Practices of face mask use and associated factors during COVID-19 pandemic among school-going children in Shimla city - Sharma, Deepak; Sharma, Naveen; Sharma, Ashna; Sood, Ambika; Sharma, Rakesh (International Journal of Research in Medical Sciences, 2022)
Background: The aim of the study was to determine the practices of face mask use and associated factors during the COVID-19 pandemic among school-going children in Shimla city. Methods: An observational study was performed in October 2021 to November 2021, with 703 students chosen using a simple random sampling procedure in Shimla city. Data was collected based on observation and analyzed using Epi info version 7. To predict the relationship between the student mask-wearing compliance and its associated factors, a univariate analysis was done. Results: A total of 703 students, 41.8% (n=294) were males while 58.2% (n=409) were females, 40.5% (n=285) <15 years while 59.5% (n=418) >15 years of age. 97.2% (n=683) were Hindu and 72% (n=506) were studying in Government schools. All of the observed (100%) were wearing masks. 76.2% (n=536) students were using cloth mask, 12.1% (n=85) N95 masks while 11.7% (n=82) surgical masks. 81.8% (n=575) covered their mouth, as well as nose, 3.7% (n=26), had masks below the chin, 2.6% (n=18) had only their mouth covered while 11.9% (n=84) had partially covered their nose. Cloth mask was considerably more used by girls besides that there was no significant difference in the type of face mask according to age, standard of class, father’s occupation and type of school. The face mask was significantly more appropriately used by the students <15 years old and studied in junior classes, there was no significant difference in mask-wearing habits according to gender, father’s occupation and type of school. Conclusions: Every student was wearing a mask, and most had good face coverage. School authorities should plan and implement IEC activities, about, types of face masks and their proper usage.